Building on #MeToo and #MeNoMore: Devising a framework to examine sexual violence in Australian music journalism. (1st June 2019) - Baker, Andrea; Williams, Katrina
Allegations against film producer Harvey Weinstein, co-owner of US entertainment company Miramax Films, which led to the revitalized #MeToo movement of October 2017, gave global recognition to the sexual violence (sexism, misogyny, sexual harassment, assault and rape) that women experience in the creative industries. As a spin-off, the #MeNoMore campaign in December 2017 resulted in more than 400 women working in the Australian music industry speaking out against similar behavior. Despite having a reputation for sexual violence, the local music press played a minor role in this hashtag development, claiming that its practices are tied to radical, liberal and progressive values. In the post-Weinstein, #MeToo and #MeNoMore era, this contradiction signifies that the Australian music press is fertile ground for a feminist investigation. However, to date minimal local research has examined the link between sexual violence and music journalism. As a literature review to a larger empirical case study, this article draws on a critical discourse analysis from the post-feminist wave of media research into rockism, poptimism, punk, rap, hip hop, dubstep and electronic dance music genres, mainly conducted in the United States and United Kingdom. Derived from this analysis, the article argues that there are four framing techniques associated with music journalism practice in Australia: gendered music press, a masculine attitude towards music reporting, gendered musical tastes and gendered sexual harassment.